Disorganisasi Keluarga Lot menurut Ekologi dan Antisipasinya bagi Keluarga Kristen - Herdemei Saerang (Voice, 2021)
Family in sociology is one of the important things. In a family there are a number of units of the smallest group that are able to instill values and norms and prevent all social problems. In the formation of Christian families, awareness of human responsibility as an extension of God's hand in the formation of an orderly world order, the role of man is very decisive. In fact, it should be the starting point for the formation of Christian families. Each Christian family is built from a person who is responsible to God as a means of establishing an orderly world order (family), and has its own role. Such awareness will form family members who are also responsible for other family members as parts of God's created world. Christian families need to understand and realize their role in the family and in the community, seeing many social problems that occur in the midst of the community environment